2019
DOI: 10.4111/icu.2019.60.4.244
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of three different luteinizing hormone-releasing hormone agonists in the chemical castration of patients with prostate cancer: Goserelin versus triptorelin versus leuprolide

Abstract: Purpose To investigate the changes in testosterone levels and rates of chemical castration following androgen-deprivation therapy (ADT) with goserelin, triptorelin, and leuprolide. Materials and Methods We retrospectively reviewed the medical records of 125 patients with prostate cancer treated with luteinizing hormone-releasing hormone (LHRH) agonists between January 2009 and December 2015. Changes in testosterone concentration during 9 months of ADT with goserelin 11.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 23 publications
1
15
2
9
Order By: Relevance
“…22,23 In Korean population, the mean serum testosterone level in patients who treated with Goserelin for 9 months was reported at 0.13 ng/mL recently. 24 In a paper analyzing the prognosis of serum testosterone and CRPC patients published by Shiota et al, 16 median pre-ART testosterone showed 0.03 ng/mL, and Sakamoto et al 15 had a median testosterone before abiraterone or enzalutamide of 0.13 ng/mL. This is…”
Section: Resultsmentioning
confidence: 94%
“…22,23 In Korean population, the mean serum testosterone level in patients who treated with Goserelin for 9 months was reported at 0.13 ng/mL recently. 24 In a paper analyzing the prognosis of serum testosterone and CRPC patients published by Shiota et al, 16 median pre-ART testosterone showed 0.03 ng/mL, and Sakamoto et al 15 had a median testosterone before abiraterone or enzalutamide of 0.13 ng/mL. This is…”
Section: Resultsmentioning
confidence: 94%
“…Европейская ассоциация урологов (EAU) также признает пороговое значение 50 нг / дл, однако считает уровень 20 нг / дл (0,7 нмоль / л) более предпочтительным [10]. В ряде клинических исследований продемонстрировано, что применение трипторелина позволяет достичь минимальных значений тестостерона в сыворотке крови <20 нг / дл [11][12][13].…”
Section: значение уровня тестостерона при андрогенной депривацииunclassified
“…Все режимы продемонстрировали сопоставимую эффективность в плане достижения уровня тестостерона <20 нг / дл, в то же время трипторелин оказался наиболее эффективным аЛГРГ в отношении снижения уровня тестостерона до <10 нг / дл (p <0,001). Через 9 мес после начала терапии аЛГРГ у 54,2 % пациентов был достигнут уровень тестостерона <10 нг / дл при применении гозерилина, у 86,4 % -при применении лейпрорелина, у 93,2 %при применении трипторелина [13]. В японском исследовании с участием 225 больных РПЖ, получавших комбинированную андрогенную блокаду и наблюдавшихся в течение 45,8 мес, многофакторный анализ показал, что уровень тестостерона <20 нг / дл является наиболее значимым прогностическим фактором общей выживаемости [12].…”
Section: значение уровня тестостерона при андрогенной депривацииunclassified
“…In einer aktuellen retrospektiven Studie von Shim et al hat Triptorelin im Vergleich zu den Agonisten Goserelin und Leuprorelin den Testosteronwert bei PCa-Patienten am effektivsten supprimiert [31]. Dieses könnte ein möglicher Erklärungsansatz für die positiveren Überlebensdaten für Triptorelin sein.…”
Section: Diskussionunclassified